2015
DOI: 10.5301/jabfm.5000233
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization of Dextran Hydrogels and Their in Vitro Release of Gentamycin Sulphate

Abstract: Scanning electron microscopy (SEM) results revealed that an increase in Dex-AE content led to an initial decrease in pore size of the Dex-AE/PEGDA hydrogels, but a further increase in Dex-AE content resulted in a slightly increase of pore size. The swelling data indicated that the swelling ratio depended on the precursor feed ratio. GS was incorporated into the hydrogels through 2 different methods, i.e., immersed and crosslinked. The crosslinked GS-Dex-AE/PEGDA hydorgels exhibited stronger antimicrobial activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…According to the FTIR of DEX-MA, the absorption bands at 1700 and 813 cm −1 ascribed to stretching vibrations of C=O and −C=CH 2 , respectively. In addition, the formation of DEX-MA was confirmed by 1 H-NMR results, 1 Figure 1D).…”
Section: Characterization Of Ccnc Dex-ma and Mpda-tpementioning
confidence: 54%
See 1 more Smart Citation
“…According to the FTIR of DEX-MA, the absorption bands at 1700 and 813 cm −1 ascribed to stretching vibrations of C=O and −C=CH 2 , respectively. In addition, the formation of DEX-MA was confirmed by 1 H-NMR results, 1 Figure 1D).…”
Section: Characterization Of Ccnc Dex-ma and Mpda-tpementioning
confidence: 54%
“…Biodegradable and biocompatible hydrogels are threedimensional molecule network with good swelling behavior in water [1][2][3]. Similar structure to the extracellular matrix environment received much attention for controlled drug carriers and tissue engineering applications [4].…”
Section: Introductionmentioning
confidence: 99%
“…Gnavi et al constructed a gelatin‐based hydrogel system loaded with vascular endothelial growth factor (VEGF) to accelerate nerve regeneration. Chang et al also found that genipin cross‐linked gelatin conduit could effectively promote peripheral nerve regeneration. Polyacrylamide (PAM) hydrogels are widely used in the field of peripheral nerve regeneration due to their good biocompatibility .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the optimization of both density and 3D distribution of such molecules in the hydrogel structure needs to be tailored to the specific tissue to be regenerated. As an example, when delivered without stabilization, growth factors diffuse rapidly, undergo denaturation and consequently lose bioactivity under normal physiological conditions [30][31][32] . The suboptimal release of growth factors, at high concentration or over a prolonged time, may lead to serious side effects, including the growth of tumors 41,42 .…”
Section: Introductionmentioning
confidence: 99%
“…The issue of recreating the ECM’s complex chemical environment might possibly be addressed by the tunable and controlled release of encapsulated bioactive agents from hydrogel matrixes 6,9,14,19,3140 , thus providing the necessary stimuli for cell migration, differentiation and production of neo-tissue growth or regeneration. The release of active molecules is limited by the difficulty of retaining their bioactivity and achieving in situ, optimal doses, gradients and timing.…”
Section: Introductionmentioning
confidence: 99%